Mechanically Driven Counter‐Regulation of Cortical Bone Formation in Response to Sclerostin‐Neutralizing Antibodies. (22nd November 2020) - Gerbaix, Maude; Ammann, Patrick; Ferrari, Serge
ABSTRACT: Sclerostin (Scl) antibodies (Scl‐Ab) potently stimulate bone formation, but these effects are transient. Whether the rapid inhibition of Scl‐Ab anabolic effects is due to a loss of bone cells' capacity to form new bone or to a mechanostatic downregulation of Wnt signaling once bone strength exceeds stress remains unclear. We hypothesized that bone formation under Scl‐Ab could be reactivated by increasing the dose of Scl‐Ab and/or by adding mechanical stimuli, and investigated the molecular mechanisms involved in this response, in particular the role of periostin (Postn), a co‐activator of the Wnt pathway in bone. For this purpose, C57Bl/6, Postn −/− and Postn +/+ mice were treated with vehicle or Scl‐Ab (50 to 100 mg/kg/wk) for various durations and subsequently subjected to tibia axial compressive loading. In wild‐type (WT) mice, Scl‐Ab anabolic effects peaked between 2 and 4 weeks and declined thereafter, with no further increase in bone volume and strength between 7 and 10 weeks. Doubling the dose of Scl‐Ab did not rescue the decline in bone formation. In contrast, mechanical stimulation was able to restore cortical bone formation concomitantly to Scl‐Ab treatment at both doses. Several Wnt inhibitors, including Dkk1, Sost, and Twist1, were upregulated, whereas Postn was markedly downregulated by 2 to 4 weeks of Scl‐Ab. Mechanical loading specifically upregulated Postn gene expression. In turn, Scl‐Ab effects on cortical bone were more rapidly downregulated in Postn −/− mice. These results indicate that bone formation is not exhausted by Scl‐Ab but inhibited by a mechanically driven downregulation of Wnt signaling. Hence, increasing mechanical loads restores bone formation on cortical surfaces, in parallel with Postn upregulation. © 2020 American Society for Bone and Mineral Research (ASBMR).